Makna Pendidikan Seksual dalam Keluarga: Perspektif Interaksionisme Simbolik - Rafi Maulana Ramadhan; Bintarsih Sekarningrum; Nunung Nurwati (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2025)
Sexual education in the family is a crucial element for sustainable human development. However, in Indonesia, this issue often encounters obstacles due to conservative norms, cultural taboos, and unequal family roles. This study aims to analyze the meaning of sexual education in Indonesian families through the lens of symbolic interactionism, which emphasizes that meaning is constructed through interaction and symbols in daily life. Employing a qualitative approach through Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), based Systematic Literature Review (SLR), 20 selected scientific articles were examined based on topic relevance and academic quality from Google Scholar and SINTA databases (2015–2025). The findings reveal: the first, the social reality of sexual education in families is hindered by patriarchal bias, parents’ low literacy, and the absence of open communication; and the second, the symbolic meaning of sexual education is transmitted through cultural symbols, traditional narratives, popular media, and non-verbal family communication. The authors argue that sexual education in Indonesian families often appears not as explicit instruction but as implicit symbolic messages that are rich in meaning yet frequently misdirected. The lack of healthy symbolic communication leads children to seek alternative meanings from external sources particularly digital media with the risk of misinformation. Therefore, fostering reflective and symbolically inclusive family communication becomes the key to building a healthy and protective understanding of sexuality.